2009
DOI: 10.1007/s00267-009-9361-1
|View full text |Cite|
|
Sign up to set email alerts
|

Plant Communities, Soil Carbon, and Soil Nitrogen Properties in a Successional Gradient of Sub-Alpine Meadows on the Eastern Tibetan Plateau of China

Abstract: To assess the recovery trajectory and self-maintenance of restored ecosystems, a successional gradient (1, 3, 5, 15, and 30 years after abandonment) was established in a sub-alpine meadow of the eastern Tibetan Plateau in China. Plant communities and soil carbon and nitrogen properties were investigated and analyzed. Regression analyses were used to assess the models (linear or quadratic) relating measures of species richness, soil carbon and nitrogen properties to fallow time. We found that species richness (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…As the richness of perennial grasses was relatively constant through time, this pattern of perennial herbs richness was caused mainly by a unimodal response of forbs richness. Similar results have been reported in restored sub-alpine meadows (Li et al 2009). …”
Section: Species Richness and Life-formssupporting
confidence: 83%
“…As the richness of perennial grasses was relatively constant through time, this pattern of perennial herbs richness was caused mainly by a unimodal response of forbs richness. Similar results have been reported in restored sub-alpine meadows (Li et al 2009). …”
Section: Species Richness and Life-formssupporting
confidence: 83%
“…Further, both leaf N and P concentrations of S. grandis decreased along the restoration gradient and its leaf N:P ratio also tended to decrease, suggesting lower access of S. grandis to both nutrients and a more strongly limited access to N relative to P. Different plant species preferentially take up different forms of N (McKane et al 2002) and the same is also likely for P (Turner 2008). This decoupling between soil inorganic nutrients and the leaf N, P and N:P ratios of the two grass species can therefore stem from potential changes in the forms of soil extractable N and P along the gradient as soil organic matter becomes progressively dominated by plant litter rather than by animal faeces (He et al 2009;Li et al 2009). Alternatively, these species-specific responses may stem from an increase in plant competition intensity along the restoration gradient (Gao et al 2009).…”
Section: Discussionmentioning
confidence: 95%
“…In the temperate steppe of Inner Mongolia for instance, grazing exclusion significantly enhances total yearly cumulative net N mineralization (Shan et al 2011). However, slower soil N mineralization rates and lower soil inorganic N availability have been reported in other restored grasslands (Baer et al 2002;Li et al 2009;MedinaRoldan et al 2012).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, studies that examine only part of the successional sequence have identify a positive (early succession), negative (late succession), or no clear relationship (transitional stage or the habitat is undergoing continuous disturbances) (Peet, ). Our previous work has shown that species richness increased in a hump‐shaped pattern, and aboveground biomass showed a linear increase along the successional gradient (Li et al ., ). Here, we examine how species diversity is related to plant biomass within different successional stages.…”
Section: Introductionmentioning
confidence: 99%